The Cambridge companion to medieval English culture - Galloway, Andrew Ed (Cambridge companions to culture., 2011)
"This "companion" is designed to introduce a range of materials deemed to constitute the culture (or, perhaps better, cultures) of medieval England, from approximately the Norman Conquest to roughly the Reformation. The fields presented here may offer a rather unusual fit with standard courses and disciplines, but the pressures on modern frameworks are intended. It is not unusual, however, for study of early periods to offer some combination of "literature," "history," "archaeology," "art history," or other field. Studies in antiquity and the Renaissance do this regularly; and medieval studies was from the outset defined in an equally capacious frame"--